EVALUATION OF THE INFLUENCE OF NOMADIC ARCHITECTURAL THINKING ON THE FUNCTIONAL EFFECTIVENESS OF MODERN MOBILE ARCHITECTURAL FORMS - Akbota Bauyrzhankyzy; Murataev Kurman Kaliyevich (Modern Scientific Technology, 2025)
This article examines the influence of nomadic architectural thinking on the functional efficiency of contemporary mobile architectural objects. The study analyzes the structural, functional, and organizational principles inherent in nomadic spatial systems and their relevance to modern architectural practice. Through the application of comparative and structural–functional analytical methods, the functional performance of mobile architectural objects is evaluated, with particular attention given to spatial flexibility, user adaptability, and functional stability. The research findings substantiate the theoretical and practical significance of nomadic architectural thinking in the development of contemporary architecture and highlight its potential as an effective framework for enhancing architectural performance